Abnormal Cardiac Autonomic Regulation in Mice Lacking ASIC3. (3rd April 2014) - Cheng, Ching-Feng; Kuo, Terry B. J.; Chen, Wei-Nan; Lin, Chao-Chieh; Chen, Chih-Cheng
Abstract : Integration of sympathetic and parasympathetic outflow is essential in maintaining normal cardiac autonomic function. Recent studies demonstrate that acid-sensing ion channel 3 (ASIC3) is a sensitive acid sensor for cardiac ischemia and prolonged mild acidification can open ASIC3 and evoke a sustained inward current that fires action potentials in cardiac sensory neurons. However, the physiological role of ASIC3 in cardiac autonomic regulation is not known. In this study, we elucidate the role of ASIC3 in cardiac autonomic function using Asic3 −/− mice. Asic3 −/− mice showed normal baseline heart rate and lower blood pressure as compared with their wild-type littermates. Heart rate variability analyses revealed imbalanced autonomic regulation, with decreased sympathetic function. Furthermore, Asic3 −/− mice demonstrated a blunted response to isoproterenol-induced cardiac tachycardia and prolonged duration to recover to baseline heart rate. Moreover, quantitative RT-PCR analysis of gene expression in sensory ganglia and heart revealed that no gene compensation for muscarinic acetylcholines receptors and beta-adrenalin receptors were found in Asic3 −/− mice. In summary, we unraveled an important role of ASIC3 in regulating cardiac autonomic function, whereby loss of ASIC3 alters the normal physiological response to ischemic stimuli, which reveals new implications for therapy in autonomic nervous system-related cardiovascular diseases.